The Causes of Urban Sprawl in Spanish Urban Areas: A Spatial Approach. Issue 2 (2nd April 2016) - Gómez-Antonio, Miguel; Hortas-Rico, Miriam; Li, Linna
Abstract: This paper explores the presence of local spatial interaction on urban development patterns of Spanish urban areas and whether this interaction might be due to the strategic behaviour of neighbouring local governments. Using remote-sensing data from aerial photography and satellite imaging along with Geographic Information Systems (GIS) techniques, it studies urban development patterns across the country with unprecedented detail. The results confirm the main hypothesis that spatial interaction exists in the levels of sprawl between neighbouring municipalities, suggesting that local governments do indeed compete for the creation of new suburban settlement developments, hence promoting excessive urban sprawl.